Beyond Anti-viral Effects of Chloroquine/Hydroxychloroquine - Gies, Vincent; Bekaddour, Nassima; Dieudonné, Yannick; Guffroy, Aurélien; Frenger, Quentin; Gros, Frédéric; Rodero, Mathieu Paul; Herbeuval, Jean-Philippe; Korganow, Anne-Sophie (Frontiers in Immunology, 2020)
As the world is severely affected by COVID-19 pandemic, the use of chloroquine and hydroxychloroquine in prevention or for the treatment of patients is allowed in multiple countries but remained at the center of much controversy in recent days. This review describes the properties of chloroquine and hydroxychloroquine, and highlights not only their anti-viral effects but also their important immune-modulatory properties and their well-known use in autoimmune diseases, including systemic lupus and arthritis. Chloroquine appear to inhibit in vitro SARS virus’ replication and to interfere with SARS-CoV2 receptor (ACE2). Chloroquine and hydroxychloroquine impede lysosomal activity and autophagy, leading to a decrease of antigen processing and presentation. They are also known to interfere with endosomal Toll-like receptors signaling and cytosolic sensors of nucleic acids, which result in a decreased cellular activation and thereby a lower type I interferons and inflammatory cytokine secretion. Given the antiviral and anti-inflammatory properties of chloroquine and hydroxychloroquine, there is a rational to use them against SARS-CoV2 infection. However, the anti-interferon properties of these molecules might be detrimental, and impaired host immune responses against the virus. This duality could explain the discrepancy with the recently published studies on CQ/HCQ treatment efficacy in COVID-19 patients. Moreover, although these treatments could be an interesting potential strategy to limit progression toward uncontrolled inflammation, they do not appear per se sufficiently potent to control the whole inflammatory process in COVID-19, and more targeted and/or potent therapies should be required at least in add-on.